THE EFFECT ANALYSIS OF THE DOUBLE-LAYER BASES IN REMOVABLE DENTURES WITH OCCLUSIVE PART ON THE MICROCIRCULATORY STATE OF THE DENTURE FOUNDATION AREA VESSELS - Yanishen, I.V.; Fedotova, O.L.; Khlystun, N.L.; Yushchenko, P.L.; Dolia, A.V. (World of Medicine and Biology, 2020)
The purpose of this work was to determine the effect of double-layer bases in removable dentures with occlusive part on the microcirculatory state of the denture foundation area vessels compared to the effect of dentures made of ordinary base resin. To achieve this purpose, 20 patients with post-traumatic defects of the maxillary bone were examined and orthopedically treated. The method of laser Doppler flowmetry was used to study the characteristics of blood circulation. The generalized analysis of microcirculatory parameters showed the absence of negative effect on the hemodynamic characteristics of the microvasculature in the denture foundation area tissues in the manufacture of removable structures with double-layer bases, which is a major factor in preventing the development of functional and structural changes that occur both from pressure and indirectly through neuroreflex mechanisms.
Keywords: microcirculation of vessels; double-layer basis; removable denture; occlusive part; mucous membrane of the oral cavity